2020
DOI: 10.31557/apjcp.2020.21.5.1465
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER-2/neu in Oral Squamous Cell Carcinoma

Abstract: Background: HER-2/neu is a member of the human epidermal growth factor (HER) family of transmembrane tyrosine kinases, which is significantly associated with the pathogenesis of various cancer types. The aim was to evaluate the expression of HER-2/neu in oral squamous cell carcinoma (OSCC) as a potential biomarker to target antigens for specific immunotherapy in OSCC. Methods: One hundred and forty histologically diagnosed OSCC cases were identified. Four to five-micrometer thick formalin-fixed, paraffin-embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…The estimated pooled prevalence of HER2 positivity in squamous CC was above 4%. Although relatively low in general, it looks slightly higher than figures reported in squamous carcinomas of other primary sites [ 101 , 102 ]. On the other hand, the non-squamous CC subgroup was composed of numerous, sometimes distinct entities ( Fig 10 and S11 File ).…”
Section: Discussioncontrasting
confidence: 55%
“…The estimated pooled prevalence of HER2 positivity in squamous CC was above 4%. Although relatively low in general, it looks slightly higher than figures reported in squamous carcinomas of other primary sites [ 101 , 102 ]. On the other hand, the non-squamous CC subgroup was composed of numerous, sometimes distinct entities ( Fig 10 and S11 File ).…”
Section: Discussioncontrasting
confidence: 55%
“…CD34 is a cluster of differentiation molecule that is seen on several cells inside the body. It is a glycoprotein that is present on the surface of the cell, which works as a cell-cell adhesion factor [ 8 , 9 , 10 ]. Cells that express CD34 are endothelial cells of blood vessels excluding lymphatics (except pleural lymphatics), mast cells, a sub-population of dendritic cells (which are factor XIIIa negative) in the interstitium and around the adnexa of the dermis of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was found that HER2 was expressed in oral cancers, and that the administration of an anti-HER2 mAb (clone H 2 Mab-19, mouse IgG 2b ) resulted in antitumor activity against HSC-2 and SAS xenografts ( 23 ). By contrast, Mirza et al ( 24 ) demonstrated that only one case out of 140 OSCCs was HER2-positive; as such, the feasibility of anti-HER2 therapy for OSCC remains uncertain. In another study, the authors developed a sensitive and specific mAb against EGFR that recognized a distinct epitope (clone EMab-17, mouse IgG 2a ) and that elicited both ADCC and CDC, as well as antitumor activity against HSC-2 and SAS xenografts ( 21 ).…”
Section: Discussionmentioning
confidence: 98%